2014
DOI: 10.1002/pbc.25322
|View full text |Cite
|
Sign up to set email alerts
|

Intensified chemotherapy without SCT in infant ALL: Results from COG P9407 (Cohort 3)

Abstract: BACKGROUND Infants with acute lymphoblastic leukemia (ALL) present with aggressive disease and a poor prognosis. Early relapse within 6–9 months of diagnosis is common. Approximately 75% of infants have MLL-rearranged (MLL-R) ALL with event free survival (EFS) ranging from 20–30%. Children’s Oncology Group (COG) P9407 used shortened (46 weeks), intensified therapy to address early relapse and poor EFS. PROCEDURE P9407 therapy was modified three times for induction toxicity resulting in three cohorts of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 42 publications
(72 reference statements)
3
53
0
6
Order By: Relevance
“…Cooperative studies showed long-term EFS of less than 50%751). Important prognostic factors found in these studies include the presence of MLL rearrangement, hyperleukocytosis, age less than three to six months, and poor response to prednisone prophase as having a clear adverse impact on outcome.…”
Section: Treatment Of Specific Subgroupsmentioning
confidence: 99%
“…Cooperative studies showed long-term EFS of less than 50%751). Important prognostic factors found in these studies include the presence of MLL rearrangement, hyperleukocytosis, age less than three to six months, and poor response to prednisone prophase as having a clear adverse impact on outcome.…”
Section: Treatment Of Specific Subgroupsmentioning
confidence: 99%
“…36 The Children's Oncology Group (COG) in North America also showed in the COG P9407 study that an EFS of 43.8% was achieved for infants >90 days old at onset of MLL-r ALL with only chemotherapy. 13 Given the experience in Europe and North America, a strategy omitting the indication of allogeneic hematopoietic stem cell transplantation (HSCT) but with the introduction of the Interfant induction followed by COG post-remission chemotherapy for MLL-r infants ≥6 months old without CNS involvement, is currently being evaluated in the Japanese nationwide MLL-10 Treatment progress in infant ALL 813 trial (UMIN000004801) conducted by the Japanese Pediatric Leukemia/Lymphoma Study Group (JPLSG).…”
Section: Chemotherapymentioning
confidence: 99%
“…[2][3][4][5] The progress in the treatment of infant ALL (diagnosed at age <12 months), however, is lagging behind compared with the treatment of children ≥1 year: EFS and OS remain at 41.7-50.9% and 44.8-60.5%, respectively (Table 1). 9,[11][12][13] In this review, advances in the pathobiology and clinical management of ALL in infants is described. …”
mentioning
confidence: 99%
“…Infant MLL-r ALL is often aggressive, and the outcomes remain poor despite intensified chemotherapy or allogeneic hematopoietic stem cell transplantation (74,75). The MLL (KMT2A) gene is a histone methyltransferase located on chromosome 11q23.…”
Section: Infant Mll-r Allmentioning
confidence: 99%